Microclimatic Studies of Grasslands In the Arid Zone of North-West India - Rao, G G.S.N; Sastry, A S.R.A.S; Krishnan, A (Annals of Arid Zone, 2016)
Microclimatological studies were carried out for a period of 3 years (1976- 1978) during summer. monsoon and post-monsoon seasons in the grassland sites at Chandan (Jaisalmer). Beechwal (Bikaner) and Palsana (Sikar) in the north-west arid zones of India. The percentage of net to total radiation was higher and the albedo v.alues were the lowest during monsoon seas n. Radiation interception during monsoon season was the lowest at Palsana grasslands sites compared to Beechwa I and Chandan. The thermal environment of grasslands of Chandan was the highest in all the seasons compared to other sites. Higher surface soil temperature (> 50Â°C) during mid-day hours coupled with higher canopy temperature resulted ill considerable heat losses through long wave radiation.